Control of Weedy Rice Infestation by Enhancing Rice Establishment in Anaerobic Direct Seeding - Vijayanathan, V. Jeyanny (2006)
Weedy rice or ‘padi angin’ is a serious threat to the rice industry of Malaysia. Its easy grain shattering characteristics has been reported to reduce rice yield up to 74%. The shift from transplanting techniques to direct seeding of planting rice has increased the weedy rice infestation. Preliminary study had shown that pre- treated rice seeds used in anaerobic seeding technique were able to out compete the growth of weedy rice and simultaneously increase the rice establishment. The objectives of this study were; a) to evaluate different rice seed germination enhancers in anaerobic (water) seeding, b) to evaluate seedling emergence in different water temperatures in anaerobic seeding and c) to evaluate rice